Supporting adjective learning across the curriculum by 5–7 year‐olds: Insights from psychological research. Issue 11 (31st October 2022) - Davies, Catherine; Syrett, Kristen; Taylor, Lucy; Wilkes, Samantha; Zuniga‐Montanez, Cecilia
Abstract: Adjectives are a powerful tool for enriching vocabulary and developing conceptual understanding. In early elementary and primary classrooms, across core and foundation subjects, children are expected to describe, measure, classify, and compare objects and events—all processes that require a mastery of adjective meanings and use. While teachers are trained in vocabulary learning, they may be less familiar with: (i) the psychological processes by which children learn adjectives, and (ii) how a focus on adjectives can support learning in domains beyond language and literacy lessons. To address these gaps, we have collaborated as a unique interdisciplinary team with linguistic, psychological, and pedagogical expertise. We synthesise research across our disciplines to provide an accessible, practical, evidence‐based primer of research findings on adjective development. We then provide guidance on how these findings can be used to enhance teaching and learning practices across subjects for children aged five to seven.